Gendered Bodies. Feminist Approaches to Spatial Design (EAAE Annual Conference Proceedings, 2023)
Looking at the Old Bauhaus of Gropius, the topic of gender equality was already present; there would be no distinction, showing a progressive vision. It was, however, equality only on paper, with little validation in practice. The New European Bauhaus reframes past ambitions, encompassing the new SDGs and assuming a crucial role in guiding spatial transformations bridging the intersection between spatial and social/gender justice. The contribution proposes to recast the discipline of architecture by its encounter with feminist methodologies, investigating through a research-by-design approach the spatialization of gender equality.